A person-centered perspective on working with people who have experienced psychological trauma and helping them move forward to posttraumatic growth - Joseph, Stephen (Taylor & Francis, 2015)
Over the past decade posttraumatic growth (PTG) has become a major topic for theory, research and practice in mainstream trauma psychology. The aim of this paper is to discuss the implications of PTG for the person-centered approach. It is argued that PTG provides a new non-medical language for understanding psychological trauma that is consistent with the person-centered approach. Person-centered personality theory provides an explanation for how PTG arises and leads to new testable predictions for research into how person-centered therapy may be able to facilitate PTG.